ЛІНГВОКУЛЬТУРА ЯК НЕВІД’ЄМНА СКЛАДОВА ВИКЛАДАННЯ ІНОЗЕМНОЇ МОВИ - Торосян О. М. (International Journal of Innovative Technologies in Social Science, 2020)
The article aims at describing main aspects of linguacultural approach to the foreign language teaching. Analyzing the key notions such as linguacultural competence, linguacultural field, linguacultural units and others, the author comes to conclusion that linguaculture is essential and integral part of the process of teaching, which enhances the efficiency of developing general communicative competence of students.